A Glossary of Historical Linguistics - Campbell, Lyle (Glossaries in Linguistics : GLLI, 2022)
Historical Linguistics - the study of language change - is a major field in linguistics. With its long history and numerous subfields of its own, Historical Linguistics provides challenges to both beginning students and scholars not specialized in this field. This Glossary meets these challenges by providing accessible and widely representative definitions, discussion, and examples of key terms and concepts used in the field. It is written by two well-known authorities in this field. The book is extremely valuable to anyone wishing to understand historical linguistic terminology and concepts.Key Features:*A handy, easily understandable pocket guide, and a valuable companion for courses in Historical Linguistics, history of individual languages, history of linguistics, and for anyone curious about how and why languages change.*Numerous cross-references to related terms*Covers new as well as traditional terminology*Not only defines, but provides examples and relevant discussion